Construction of a Two-Gene Immunogenomic-Related Prognostic Signature in Lung Squamous Cell Carcinoma - Zhang, Xiaoting; Xiao, Jing; Fu, Xian; Qin, Guicheng; Yu, Mengli; Chen, Guihong; Li, Xiaofeng (Frontiers in Molecular Biosciences, 2022)
Lung cancer has the highest tumor incidence in China. Lung squamous cell carcinoma (LUSC) is the most common type, accounting for 40%~51% of primary lung cancers. Lung squamous cell carcinoma is slow in growth and late in metastasis. Immune-related genes (IRGs) and immune infiltrating cells play vital role in the clinical outcomes of LUSC. It is important to systematically study its immune gene map to help the prognosis of cancer patients. In this study, we combined the prognostic landscape and expression status of immune-related genes (IRGs) downloaded from the TCGA and InnatedDB databases and systematically analyzed the prognostic information of LUSC patients to obtain immune-related genes. After systematically exploring the survival analysis, prognosis-related genes were found, and the PPI network revealed that a total of 11 genes were hub genes. By multivariate Cox analysis, a two-gene prognosis risk model was established. Two IRGs were closely correlated with the prognosis of LUSC. Based on these two genes, a new independent prognostic risk model was established, and this model was further verified in the GEO database. Moreover, the risk score of the model was correlated with sex, survival status and lymphatic metastasis in LUSC patients, and the predictive risk of the prognostic risk model was significantly positively correlated with the 5 kinds of immune cells (CD4 T cells, CD8 T cells, neutrophils, macrophages, and dendritic cells). This study comprehensively analyzed immunogenomics and presented immune-related prognostic biomarkers for LUSC.